An Ultrastable, Small Ag75+ Nanocluster within a Triangular Hollow Polyoxometalate Framework. Issue 38 (10th July 2020) - Yonesato, Kentaro; Ito, Hiroyasu; Yokogawa, Daisuke; Yamaguchi, Kazuya; Suzuki, Kosuke
Abstract: Small Ag n nanoclusters ( n <10) have been emerging as promising materials as sensing, biolabeling, and catalysis because of their unique electronic states and optical properties. However, studying synthesis, structure determination, and exploration of their properties remain major challenges as a result of the low stability of small Ag nanoclusters. Herein, we synthesized an atomically precise face‐centered‐cubic‐type small Ag7 5+ nanocluster supported by a novel triangular hollow polyoxometalate (POM) framework [Si3 W27 O96 ] 18− . The cluster showed unique Ag7 5+ ‐to‐POM charge transfer bands in both visible and UV light regions. Furthermore, this small Ag7 5+ nanocluster exhibited an unprecedented ultrastability in solution, despite having exposed Ag sites that can be accessed by small molecules, such as O2, water, and solvents. Abstract : You got the silver : An ultrastable, small Ag7 5+ nanocluster was synthesized within an unprecedented triangular hollow polyoxometalate (POM) framework [Si3 W27 O96 ] 18− . The cluster showed unique Ag7 5+ ‐to‐POM charge transfer bands in both visible‐ and UV‐light regions.